P176 An EEG-TMS study investigating the oscillatory signatures underlying the time course of reflexive visuospatial attention. Issue 3 (March 2017) - Ahrens, M.-M.; Veniero, D.; Harvey, M.; Thut, G.
Abstract : Question: Oscillatory brain activity in specific frequency bands has been related to cognitive processes such as attention (Foxe and Snyder (2011) Front Psychology 2:154). While in the domain of endogenous top-down control of visuospatial attention, occipito-parietal oscillations in the alpha band have been causally implicated (Romei et al. (2010) Journal of Neurosci. 30(25):8692–8697), the oscillatory signatures underlying reflexively driven orienting of spatial attention and its time course remain unclear. In this study, we employed electrophysiology (EEG) and concurrent single pulse transcranial magnetic stimulation (TMS) during a cued visuospatial detection task, known to induce reflexive shifts of attention and inhibition-of-return (IOR). Methods: Participants ( n = 13) performed an exogenously cued dot detection task while the time course of the IOR was measured at four different cue-target delays (from 105.8–705.8 ms). The cue consisted of a brief flash in the left or right visual field and was task-irrelevant and uninformative as to forthcoming target location. In one quarter of the trials a single pulse TMS was delivered over the right intraparietal sulcus (IPS) at the longest cue-target delay (705.8 ms) whilst changes in brain activity were measured with EEG. Results: The behavioural analysis revealed significantly faster reaction times to targets at cued relative to uncued positions at the early cue-target delay, which reversed to significantly faster reaction times to uncued relative to cued positions (i.e, an IOR) at the later cue-target delays. Ongoing analyses of the EEG measurements focuses on identifying the key frequency bands implicated in reflexive shifts of attention in TMS-free trials, complemented by analyses of the oscillatory response to single-pulse TMS over the right parietal cortex at the maximal time of IOR. Conclusions: Our behavioural findings reveal that our experimental manipulation induced a reflexive shift of attention as expected, allowing us to examine the EEG/TMS-EEG data for underlying oscillatory brain activities.